Antimicrobial Resistance in Swine and Cattle Farms - Bruna F. Pinto; Sara A. M. Silva; Inês C. Rodrigues; J. M. Lopes-Jorge; J. Niza-Ribeiro; Joana C. Prata; Paulo Martins da Costa (Microbiology Research)
Antimicrobial resistance is increasingly becoming a serious public health issue. There is scientific evidence linking the use of antibiotics in livestock production to the emergence and spread of resistance in bacteria that are important for human health. To assess the prevalence of antimicrobial resistance in Escherichia coli and Enterococcus spp., fecal and slurry wastewater samples were collected from various cattle and swine farms, mainly located in the northern and central regions of Portugal. Samples from each farm were pooled for microbiological processing to isolate Escherichia coli and Enterococcus spp., followed by specific antibiotic susceptibility testing for each species using the disk diffusion method. The results of these analyses indicated a significant issue with tetracycline resistance in E. coli and Enterococcus spp. Furthermore, a notably higher frequency in resistant strains was observed in the majority of slurry samples compared to those derived from swine feces. This observation led to the hypothesis that slurry may provide a comprehensive historical perspective for studying the antibiotic resistance patterns present on a farm.